PENGATURAN ANGGARAN PENDAPATAN DAN BELANJA NEGARA MELALUI PERATURAN PEMERINTAH PENGGANTI UNDANG-UNDANG - Moh Rizaldi (Legacy: Jurnal Hukum dan Perundang-Undangan, 2021)
It is still a matter of debate whether the State Revenue and Expenditure Budget can be regulated by government regulation in lieu of law. For the pros, this arrangement can be done because it is based on the suitability of types, hierarchies and content material. Meanwhile, for those who are contra, this arrangement violates the principle of people"s sovereignty and checks and balances. Not taking part in the debate, President Jokowidodo actually changed the State Budget Law through a Presidential Regulation. This paper criticizes the President"s actions as well as provides a solution to it by offering ideas in the form of amendments to the State Budget Law through government regulation in lieu of law. The problems raised in this research are, first, what limitations should be made to overcome the open-ended nature of Article 22 of the 1945 Amendment so that the President does not take excessive action? Second, is it necessary to amend the state budget Law through government regulation in lieu of law? This is doctrinal research. Through a statutory approach and conceptual approach, this paper concludes that first, limitation can be done by limiting the scope of the meaning of urgency that forces it and the material is limited to state administration only. Second, in an emergency situation, the existence of government regulations in lieu of law is needed to amend the state budget Law.